Investments in watershed services: understanding a new arena of environmental governance in the western United States - Huber-Stearns, Heidi Rebecca, author; Cheng, Antony S., advisor; Schultz, Courtney, committee member; Reid, Robin, committee member; Seidl, Andrew, committee member (Colorado State University. Libraries, 2015)
Issues around sustainably managing freshwater resources are one of the most challenging and timely issues affecting the globe. In response to rising social and ecological complexities, decision makers are faced with designing new policies and programs to effectively govern water resources. This shift towards new freshwater resource management approaches is in line with recent movement toward incentive-based mechanisms such as “Investments in Watershed Services” (IWS). The western United States contains one of the most concentrated IWS populations, in a time when population growth, intensifying land uses, and climate-induced environmental changes are stressing ecological systems in the region. My dissertation focuses on understanding this new arena of environmental governance aimed at freshwater conservation in the US West. Through three sets of data and analytical lenses I explore: the characterization of this new arena of governance, what led to its recent and significant growth, and what changes have occurred with respect to how such water resources were traditionally governed. I employ a mixed methods approach, using quantitative approaches to characterize the study population and temporal changes, and qualitative approaches to dive deeper into understanding specific phenomena. First, I improve understanding of IWS as an institution, and demonstrate the importance of dynamics between institutional factors for external context, program structure, and other related analytical domains in shaping how PWS is applied to water resources challenges globally. Through an institutional analysis of IWS and the use of cluster analysis to group programs around buyer types and management actions, I highlight the role of government, influence of geographic context, and role of both regional and local conditions in shaping IWS design and structure. Second, I demonstrate that government actors are essential to IWS in the region, expanding beyond existing regulations and traditional roles. This exploration of the role of government within adaptive governance shows the evolving and expanding role of government over time, from federal regulations driving early water quality management, then state legislation driving water quantity programs, and more recently, federal agencies partnering on local water source protection efforts. Third, I show how key individuals and organizations create voluntary IWS in response to risk, aligning policies, politics and problems into solution framing, which suggests policy process theories more explicitly consider social-ecological complexities. These programs constitute the most recent expansion of IWS in the US West, and applying a policy process theory sheds light into the formation of the IWS, and the political, economic, ecological and social components that aligned to make the programs possible. My research shows this new arena of environmental governance as adaptive, place and problem-based, learning and collaboration-focused, accepting of uncertainty, and containing nimble and adaptive government across scale. My work also creates a baseline of IWS in the region, and identifies areas for future research as IWS matures over time.